DETERMINING AN OPTIMAL CORN PLANTING SCHEDULE BY USING THE INTEGRATION OF SUPPLY CHAIN RISK EVALUATION MODEL - Suharjito, Machfud, Bambang Haryanto, Sukardi (Department of Agroindustrial Technology, Bogor Agricultural University, 2010)
ABSTRACT Inappropriate pattern of plant scheduling will cause the production declining and supplies inconsistency, and then it can cause the product accumulation that influences the price decreasing. That risk was not only suffered by the producer but also would influence the achievement of the other organization that connected in the supply chain network. Therefore, there should be an optimal scheduling management to be able to solve the possibility of the risks. This paper described a model of supply chain risk management to get an optimum solution of choosing the pattern of plant scheduling especially in corn commodity with the qualitative and quantitative approaches. The quantitative model was approached with the MILP method (Mixed Integer Linear Programming), the qualitative model using AHP (Analytic Hierarchy Process) and the integration model was developed by using weighted sum method. The verification results of this approach was obtained parreto values that could be used by decision makers to determine optimal planting schedules based on the multi criteria of qualitative and quantitative objective function.Keywords: supply chain risk, planted scheduling pattern, integration optimization model.